Photo-induced sequence defined macromolecules via hetero bifunctional synthons. Issue 10 (19th December 2014) - Zydziak, Nicolas; Feist, Florian; Huber, Birgit; Mueller, Jan O.; Barner-Kowollik, Christopher
Abstract : We report the first photochemical protocol for the generation of sequence defined macromolecules employing two hetero bifunctional photoreactive synthons, exploiting the orthogonal nature of photochemical – via the use of caged dienes – and thermally driven ligation protocols. Abstract : We report the first photochemical protocol for the generation of sequence defined macromolecules employing two hetero bifunctional photoreactive synthons, exploiting the orthogonal nature of photochemical – via the use of caged dienes – and thermally driven ligation protocols. We demonstrate that the iterative alternating synthon addition to an initial bifunctional core under irradiation at ambient temperature enables the generation of a macromolecule with up to 10 units ( M = 3231.58 g mol −1, Đ = 1.00). The resulting macromolecules are monodisperse and feature absolute chain end fidelity. The unit-by-unit construction of the macromolecule is evidenced by Nuclear Magnetic Resonance Spectroscopy, Electrospray Ionization Mass Spectrometry and Size Exclusion Chromatography. The fundamental principle demonstrated herein paves the way for employing photochemical strategies for the design of sequence defined polymers.